2014
DOI: 10.1016/j.pgeola.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Geological interpretation of current subsidence and uplift in the London area, UK, as shown by high precision satellite-based surveying

Abstract: Long term planning for flood risk management in coastal areas requires timely and reliable information on changes in land and sea levels. A high resolution map of current changes in land levels in the London and Thames estuary area has been generated by satellite-based persistent scatterer interferometry (PSI), aligned to absolute gravity (AG) and global positioning system (GPS) measurements. This map has been qualitatively validated by geological interpretation, which demonstrates a variety of controlling inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
(67 reference statements)
5
19
0
Order By: Relevance
“…It is also noteworthy that the width of the Thames floodplain increases markedly downstream of the Wimbledon Fault, as shown by the outcrop of the Holocene deposits. Our PSI data confirm the observations for domain '5A' identified by ALDISS et al (2014), who found velocities of -1.55 ± 0.83 mm/year for this area during 1997-2005, with the largest subsidence rates centred close to the Merton Abbey public water supply well. Ground motions in this area were attributed to groundwater abstraction from the above water well, and were investigated further in the framework of the ESA Terrafirma project, via the production of the Terrafirma-London H3 Modelled Product (BATESON et al 2009).…”
Section: Groundwater Abstraction and Risesupporting
confidence: 90%
See 3 more Smart Citations
“…It is also noteworthy that the width of the Thames floodplain increases markedly downstream of the Wimbledon Fault, as shown by the outcrop of the Holocene deposits. Our PSI data confirm the observations for domain '5A' identified by ALDISS et al (2014), who found velocities of -1.55 ± 0.83 mm/year for this area during 1997-2005, with the largest subsidence rates centred close to the Merton Abbey public water supply well. Ground motions in this area were attributed to groundwater abstraction from the above water well, and were investigated further in the framework of the ESA Terrafirma project, via the production of the Terrafirma-London H3 Modelled Product (BATESON et al 2009).…”
Section: Groundwater Abstraction and Risesupporting
confidence: 90%
“…3.2.2). This geohazard polygon also corresponds well with domain '6C' identified by ALDISS et al (2014).…”
Section: Underground Constructionsupporting
confidence: 76%
See 2 more Smart Citations
“…The rates of deformation in this study are aligned to previous investigations which have used PSI to monitor earth surface movement in the UK [18]. Apart from [20,25], there is limited work reporting investigation of the relationships between major soil group type and infrastructure movement using PSI, particularly in the UK, so limited direct comparisons can be made.…”
Section: Discussionsupporting
confidence: 64%